The Essence of Human Resources Management - Jaas , Allam (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2022)
The current research aims at identifying the essence of human resource management, recognizing the management through examining the importance of management, whose target is to establish an ongoing cooperative social entity with an objective and purpose. Furthermore, it seeks to discover the principles of management and the significance of human resource in the institution, and to demonstrate the prominence of human resource study and the historical development of human resource management. The administration in its modern form is the result of a number of overlapping changes and developments dating back to the beginning of the industrial revolution. So, the study of the most important historical stages of the administration is beyond doubt very crucial, let alone the demonstration of the objectives of human resource management whether social, economic, ethical, organizational, functional, personal or global. It also looks into human resource management decisions, the most important of which were individual and collective decisions. In addition, I will clarify the functions and work of human resource management such as recruitment, training, wage determination, worker relationships, workforce planning and importance. I will conclude the research by emphasizing that people with modern trends see the organization as having many functions, like production, marketing, accounting, finance and others. Besides, human resource management is also a key function of the organization, just as other functions in the organization are. This is because of the importance of the part of the human resource through its role and the work and tasks it accomplishes in the organization. The major point of the research is that the management in its modern form is the upshot of many changes and developments and has taken several names from personnel management to employees’ management to human resource management.